Patient response to osteotomy around the knee joint at one year post-operation—fulfilment of expectations and current health status - Grünwald, Leonard; Schröter, Steffen; Dickschas, Jörg; Harrer, Jörg; Minzlaff, Philipp; Hinterwimmer, Stefan; Saier, Tim; Pattappa, Girish; Angele, Peter (Archives of Orthopaedic and Trauma Surgery, 2023)
Introduction: The aim of this study was to investigate patient satisfaction and fulfilment of expectations after osteotomy around the knee at one year postoperatively, using patient-related outcome measures. Materials and methods: From the initial sample of 264 patients, a total of 132 patients (age 48y ± 11) were enrolled in this prospective study (response rate 49.3%). Data were collected using the Hospital For Special Surgery-Knee Surgery Expectations Survey (HFSS-KSES), items for satisfaction and the Knee injury and Osteoarthritis Outcome Score (KOOS) measures. At one year postoperative follow-up, an individualized questionnaire asked whether the specific person-related expectations had been fulfilled. Results: Satisfaction was high with 83.2% of all participants at one year after surgery. A total of 78% of patients stated they would decide to do the surgery again. This decision was significantly associated with satisfaction, younger age and better KOOS scores scales before surgery for pain, activity and sports. We found high correlations between satisfaction and fulfilment of expectations for the HFES-KSES. Fulfilment of expectations one year after surgery was significantly associated with significant improvements in KOOS scales at one year post-operation. Expectations (1) “to get the knee back to normal status”, (2) “improve ability to squat”, (3) “improve ability to run”, (4) “improve ability to kneel” had been fulfilled worst. A multiple linear regression model for satisfaction had an R2 = 0.797 of the variance. The most influential was the variable fulfilment of “maintain health” that had 70.7% of variance. Conclusions: The fulfilled expectation concerning an improvement of the ability to maintain health was the most influential parameter for satisfaction at one year post-osteotomy. Patients with better health status of the knee and younger age rated the surgery to be more positive and were also more likely to do the surgery again. This provides an indication for an earlier intervention, before the knee and overall health status becomes more detrimental. Level of evidence: Level II (Therapeutic study).
CRIS-Team Scopus Importer:2023-07-21
Keywords: Expectation; HTO; Knee; Osteotomy; Satisfaction